Pemanasan Global: Faktor, Dampak dan Upaya Penanggulangan - Jefri Kurniawan; Abdul Razak; Nurhasan Syah; Skunda Diliarosta; Aulia Azhar (Yayasan Literasi Sains Indonesia, 2024)
Nowadays, the world's attention is focused on the problem of global warming. This is because global warming contributes to ecosystem changes. The article reviews the factors that cause global warming, how the impacts are caused from various aspects including elevated sea levels, unpredictable weather patterns, and disasters caused by nature, disruption to productivity and crops, health problems and decreased biodiversity. Furthermore, this paper reviews what efforts can be made to mitigate global warming. This article uses a literature review method that synthesizes several international articles as reference information related to global warming. The study's findings indicate that the primary factors causing global warming are the increase in greenhouse gases and deforestation. This factor has an impact on ecosystem changes so that it has a high urgency in overcoming it. Mitigation efforts to address global warming include conventional mitigation strategies, negative emission technologies, and innovative geoengineering approaches. In addition, it requires seriousness and diplomatic cooperation from various parties in efforts to mitigate the impacts caused.